2021
DOI: 10.1080/10903127.2021.1977876
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 on EMS Refresher Course Completion and Delivery

Abstract: Introduction: The COVID pandemic has significantly impacted educational development and delivery, yet there is little quantitative research on this topic. The primary objective of this study was to compare the total number of Emergency Medical Service (EMS) Refresher (ER) course completions during 2020 versus prior years. Secondary outcomes examined in person versus online/distributive learning during the study period.Methods: The Commission on Accreditation for Prehospital Continuing Education (CAPCE) is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“… Transport 42 March et. al 54 Effects of COVID-19 on EMS Refresher Course Completion and Delivery Case Commission Accreditation for Prehospital Continuing Education database of continuing education records US ● There was a 179% increase in completion of EMS refresher courses from 2018 to 2020. ● There was a 185% increase in asynchronous online refresher course completion from 2018 to 2020.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Transport 42 March et. al 54 Effects of COVID-19 on EMS Refresher Course Completion and Delivery Case Commission Accreditation for Prehospital Continuing Education database of continuing education records US ● There was a 179% increase in completion of EMS refresher courses from 2018 to 2020. ● There was a 185% increase in asynchronous online refresher course completion from 2018 to 2020.…”
Section: Resultsmentioning
confidence: 99%
“… 23 With regard to continuing education, the Commission on Accreditation for Prehospital Continuing Education (CAPCE) saw a 179% increase in EMS refresher courses during 2018 to 2020, with a 185% increase in asynchronous online learning. 54 This may suggest that distance learning as a method for recertifying provider credentials may increase rates of recertification, in contrast with in-person continuing education programs.…”
Section: Discussionmentioning
confidence: 99%
“…A small preliminary study from the US found that Advanced Trauma Life Support (ATLS) course outcomes were better on a new hybrid e-learning course post-pandemic compared to a face-to-face course pre-pandemic 35 . A large observational study of emergency medical service refresher courses also found that COVID-19 caused a post-pandemic surge in course numbers and an almost total transition towards e-learning courses, but it did not investigate course outcomes directly 36 . The declining performance that we have identified on our ALS course is likely representative of the system-wide effect of COVID-19 on medical education, rather than anything specific to the ALS course.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they found university medical students to have increased knowledge regarding EMS roles and responsibilities, which may have beneficial implications for transfer of care (23) . With regard to continuing education, the Commission on Accreditation for Prehospital Continuing Education (CAPCE) saw a 179% increase in EMS refresher courses during 2018 to 2020, with a 185% increase in asynchronous online learning (54) . This may suggest that distance learning as a method for recertifying provider credentials may increase rates of recertification, in contrast with in-person continuing education programs.…”
Section: Discussionmentioning
confidence: 99%